Energy Management in the Large-Scale Manufacturing (LSM) Industries of Pakistan; Current Status, Barriers and Drivers - Muhammad Muneeb Ahmad (00000206086); Dr. Muhammad Bilal Sajid (USPCAS-E, NUST, Islamabad, 2021)
TH-301
Keywords: MS-TEE Thesis